Electron affinities of [5, 6]-open and [5, 6]-closed adducts of trifluoromethylfullerene Cs-C70(CF3)8: even one bond matters!. (10th February 2016) - Rybalchenko, Alexey V.; Apenova, Marina G.; Semivrazhskaya, Olesya O.; Belov, Nikita M.; Markov, Vitaliy Yu.; Troyanov, Sergey I.; Ioffe, Ilya N.; Lukonina, Natalia S.; Sidorov, Lev N.; Magdesieva, Tatiana V.; Goryunkov, Alexey A.
Highlights: Crucial influence of open-closed skeletal transitions on the electronic properties of fullerene was demonstrated. Electrochemically promoted switching of electronic properties based on disruption of the conjugated 62π-electron system into the isolated 32 and 28π-electron fragments upon closing the [5, 6]-bond in question. Regioselective near-equatorial cycloproponation of trifluoromethylfullerene C s -C70 (CF3 )8 was elaborated. More compact alternatives promising molecular switching capabilities can be found within the family of pyramidalized polyenes. Abstract: Despite trifluoromethylfullerene C s -C70 (CF3 )8 has a multitude of available reaction sites, [2 + 1] cycloaddition of CX2 moieties (X = F and p -MeOC6 H4 ) proceeds regioselectively at a particular [5, 6]-bond. Depending on the nature of X, the resulting derivative can be either [5, 6]-open (i.e., the said CC bond is cleaved) or [5, 6]-closed, and this structural detail, seemingly insignificant for a molecule that large, brings about a remarkable 0.6 eV difference in the electron affinity, as revealed by electrochemical studies. Synthesis, structural and electrochemical elucidation of the C70 (CF3 )8 (CX2 ) compounds are discussed, as well as electrochemically promoted switching of the electronic properties based on disruption of the conjugated 62π-electron system into the isolated 32 and 28π-electron fragments upon closing the [5, 6]-bond.